Practical Biogas Production-Based Environmental Education for Students at State Junior High School 3 in Bengkulu City - Rosane Medriati; Desy Hanisa Putri; Tiara Hardyanti Utama; Netriani Veminsyah Ahda; Dennis Jovani Harryson Siregar; Ahmad Khairul Pajri; Syed Jawad Zaren; Jarwati Ayuna Putri (CV Media Inti Teknologi, 2026)
Background: Strengthening renewable energy literacy at the secondary education level is a strategic step toward fostering students’ ecological awareness and environmental conservation skills. Biogas, as an alternative energy source derived from organic waste, holds great potential for integration into hands-on learning to enhance students’ conceptual understanding and scientific skills.Objectives: This community service activity aims to introduce biogas technology through hands-on, practice-based education and to analyze students’ responses to the implementation of environmental learning.Methods: The implementation followed a comprehensive pedagogical framework consisting of lectures, interactive discussions, and demonstrations, complemented by hands-on biogas production practices. The program involved 50 students who actively participated in all learning activities and practical sessions throughout the implementation process. Students utilized simple teaching aids crafted from fruit waste and microbial activators (molasses and EM4), with program efficacy evaluated through pre-tests, post-tests, and student response assessments.Results: The activity resulted in a measurable increase in students’ knowledge and skills regarding waste categorization and organic waste management. Participants successfully demonstrated an understanding of the fermentation process required to convert organic waste into methane gas using simple teaching aids.Conclusion: The integration of practical biogas technology into the secondary curriculum effectively bridges the gap between theoretical ecological concepts and real-world environmental skills. Both teachers and students benefited from the hands-on approach, proving that localized renewable energy innovations are viable tools for enhancing scientific literacy.